The Causality Between Economic Growth and Immigration in Germany and Switzerland - González-Gómez, Manuel; Otero Giráldez, Mª Soledad (Economic & Social Studies, 2011)
This paper analyses the relationship between immigration and the economic growth in Germany and Switzerland during the period 1970-2005 by using a cointegration approach. Both countries have gone through a similar learning process. First they encouraged low-skilled and temporary workers. More recently, they have attracted high-skilled people and restricted the recruitment of low-skilled immigrants. Our empirical analysis reveals important differences between Germany and Switzerland. The results may be useful for other countries that attract immigrants to compensate for shortages in the labour market and in response to the ageing of the population.
Keywords: immigration; Germany; Switzerland; economic growth